2023
DOI: 10.1007/s13679-023-00509-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nutrition and Exercise Interventions on Persons with Sarcopenic Obesity: An Umbrella Review of Meta-Analyses of Randomised Controlled Trials

Abstract: Background Sarcopenic obesity (SO) is an increasing phenomenon and has been linked to several negative health consequences. The aim of this umbrella review is the assessment of effectiveness and certainty of evidence of nutrition and exercise interventions in persons with SO. Method We searched for meta-analyses of RCTs in PubMed, EMBASE and CENTRAL that had been conducted in the last five years, focusing on studies on the treatment and prevention of SO. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Moreover, increased physical activity in elderly Canadian individuals is associated with higher lean mass and lower fat mass [ 15 ], and Germans aged 50 years and above with moderate weekly activity had lower odds of low handgrip strength [ 22 ]. Notably, resistance training has been reported as an intervention method for improving muscle function in individuals with sarcopenic obesity [ 32 ]. In adults with sarcopenic obesity, resistance exercise reduces fat mass and improves grip strength, and the combination of aerobic and resistance exercises leads to decreased fat mass and improved walking speed [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, increased physical activity in elderly Canadian individuals is associated with higher lean mass and lower fat mass [ 15 ], and Germans aged 50 years and above with moderate weekly activity had lower odds of low handgrip strength [ 22 ]. Notably, resistance training has been reported as an intervention method for improving muscle function in individuals with sarcopenic obesity [ 32 ]. In adults with sarcopenic obesity, resistance exercise reduces fat mass and improves grip strength, and the combination of aerobic and resistance exercises leads to decreased fat mass and improved walking speed [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, patients with history of smoking, drinking, diabetes, high tumor stage, malnutrition and low exercise ability should be given corresponding nutrition and exercise intervention according to the actual situation of the patients (41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the limited number of primary studies, the certainty of evidence ranged from moderate to very low. Despite this uncertainty, the study suggested that resistance training could be a beneficial intervention for individuals with SO, particularly for enhancing muscle function [ 30 ].…”
Section: Reviewmentioning
confidence: 99%
“…While the most recent article among the top 15 most cited was published in 2018, it is crucial to acknowledge the continued significance of relevant articles published after this year. Several important studies referenced in our work were published post-2018 [ 28 - 30 ]. Furthermore, Figures 15 - 18 highlight the keyword "bariatric surgery."…”
Section: Reviewmentioning
confidence: 99%